Development and Evaluation of Game-Based Learning System Using the Microsoft Kinect Sensor - Chih-Hsiao Tsai; Yin-Hao Kuo; Kuo-Chung Chu; Jung-Chuan Yen (International Journal of Distributed Sensor Networks)
This paper investigates the capability of Kinect sensor as interactive technology and discusses how it can assist and improve teaching and learning. The Kinect sensor is a motion sensor that provides a natural user interface. It was implemented by Microsoft for the Xbox 360 video-game console to create a new control-free experience for the user without any intermediary device. The Kinect sensor can enhance kinesthetic pedagogical practices to profit learners with strong bodily-kinesthetic intelligence (body smart). As a learning tool, the Kinect sensor has potential to create interactive games, to increase learner motivation, and to enhance learning efficiency via its multimedia and multisensory capacity. Many students must learn spatial skills to improve learning achievement in science, mathematics, and engineering. This paper will focus on developing the Kinect sensor-assisted game-based learning system with ARCS model to provide kinesthetic pedagogical practices for learning spatial skills, motivating students, and enhancing students’ effectiveness. The responses to the System Usability Scale indicated that our system demonstrated usability and learnability. We conclude that the Kinect sensor-assisted learning system promotes the development of students’ spatial visualization skills and encourages them to become active learners.